Modification of Diffusion Layers by Laser Shock Peening - Prochazka, Jiri; Vilis, Jindrich; Dobrocky, David; Sperka, Petr (Manufacturing Technology Journal, 2023)
The article deals with a possibilities of an enhancement of functional properties of highly stressed components by specific combination of surface technology. Two surface technologies such as plasma nitriding and laser shock peening were selected for the experiment. Those technologies were applied upon steel 42CrMo4 frequently utilized in manufacturing of strained components. Properties obtained by applied surface technologies were tested by following experimental methods. The chemical composition was verified by optical emission spectrometer Tasman Q4 Bruker. The surface morphology was inspected by scanning electron microscope TESCAN MIRA 4. The microstructure of heat treated as well as of nitrided specimens was observed by opto-digital microscope Olympus DSX500i. The microhardness profiles were measured by microhardness tester LM247 AT LECO. The friction coefficient was tested on tribometer Bruker UMT 3 TriboLab. For an assessment of the surface wear resistance the profilometer Talysurf CLI 1000 and Contour GT were utilized. The experimental results show that although the proposed surface technology combination manifests itself to be disadvantageous, both technology LSP, as well as plasma nitriding, applied separately, can lead to a significant wear reduction.
Keywords: Wear resistance; Plasma nitriding; Laser shock peening; Highly stressed components